Corporate Social Responsibility (CSR) influence on brand equity in energy sector: a case on Chevron Bangladesh - Ananta, Antara Tarannum (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.